**If**

*i*= √-1, which of the following expressions shows the square of the sum (2*i*+ 3) + (2 – 6*i*)?
A. 41 + 40

*i*
B. 9 + 40

*i*
C. 41 – 40

*i*
D. 9 – 40

*i*
You may be tempted to square the sum right away, but it
is simpler to add the numbers before squaring them. The sum is 2 + 3 – 6

*i*+ 2*i*= 5 – 4*i*. Squaring this result produces 5 • 5 + 2 • 5 • (-4*i*) + (-4*i*) • (-4*i*) = 25 – 40*i*+ 16*i*^{2}= 25 – 40*i*+ 16(-1) = 25 – 16 – 40*i*= 9 – 40*i*. Thus the correct choice is (D).
______________________________________________

## No comments:

## Post a Comment